Booklet Resep Berbahan Dasar Ikan Sebagai Upaya Pencegahan Stunting di Desa Tambong Banyuwangi - Astri Iga Siska; Novilia Kareja; Sandryas Alief Kurniasanti (I-Com: Indonesian Community Journal, 2024)
Based on information from the Banyuwangi Health Service, the incidence of stunting in 2023 was recorded at approximately 2,300 children, this number is known to have decreased significantly from the number of 2,780 stunted children recorded in 2022. This community service aims to address issues related to stunting which are of particular concern, especially in the health sector in Banyuwangi. Stunting prevention can be done by providing education to mothers regarding the provision of healthy and nutritious food. One of the healthy foods in question is fish-based food. Through this activity, PKK mothers from Tambong Village were trained in processing fish products into nutritious food for children, preventing stunting. They were also given a booklet of fish-based recipes to apply at home. The training and mentoring process involved preparation, socialization of fish utilization in preventing stunting, training in processing fish-based food, and evaluation. The results showed that participants gained knowledge and skills related to fish-based food processing, and were enthusiastic about making these processed foods for children's meals.